Simplify 2(5(x+y)-2(3x+y)) and 5(3a-2a(3a+6b)+6a^2)

2 Answers | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

The expressions 2(5(x+y)-2(3x+y)) and 5(3a-2a(3a+6b)+6a^2) have to be simplified.

2(5(x+y)-2(3x+y))

= 2(5x+5y-6x-2y)

= 2(-x+3y)

= -2x + 6y

5(3a-2a(3a+6b)+6a^2)

= 5(3a-6a^2 - 12ab +6a^2)

= 5(3a - 12ab)

= 15a - 60ab

The simplified form of 2(5(x+y)-2(3x+y)) = -2x + 6y and 5(3a-2a(3a+6b)+6a^2)= 15a - 60ab

atyourservice's profile pic

atyourservice | Student, Grade 11 | (Level 3) Valedictorian

Posted on

`2(5(x+y)-2(3x+y)) `  distribute the numbers outside of the parenthesis

`2(5x+5y-6x-2y) `   multiply the number inside by 2 or you can add like terms then multiply by 2

`(10x+10y-12x-4y)`    `(10x-12x+10y-4y)`   -2x+6y

do the same thing here

`5(3a-2a(3a+6b)+6a^2)`

`5(3a-6a^2-12ba+6a^2)`

`5(3a-6a^2+6a^2-12ba) `         `5(3a-12ba) `     15a-60ba

We’ve answered 318,915 questions. We can answer yours, too.

Ask a question